Follow-up analysis of third cycle graduates from the basic rural general education (Praxis Educativa, 2012)
This Research Project focused on the characteristics of students who had completed their third course of studies in rural. BGE and had continued studying in urban Polimodal Education institutions. The samples were institutions belonging to the Supervision of the IV Region in Chubut, both in rural and urban areas. Public policies have decided what, what for, how and when children from rural areas should learn. These policies have ignored cultural differences, social status, way of life, motivation and special interests. Pedagogical practice is still structured according to past socio-cultural categories and institutions have modernity features. It is necessary to give solutions to the educational needs in rural areas, taking into account the special social context of each community so as to foster and enrich their culture and generate anapproximation to BGE. BGE and had continued studying in urban Polimodal Education institutions. The samples were institutions belonging to the Supervision of the IV Region in Chubut, both in rural and urban areas. Public policies have decided what, what for, how and when children from rural areas should learn. These policies have ignored cultural differences, social status, way of life, motivation and special interests. Pedagogical practice is still structured according to past socio-cultural categories and institutions have modernity features. It is necessary to give solutions to the educational needs in rural areas, taking into account the special social context of each community so as to foster and enrich their culture and generate anapproximation to BGE.
Keywords: BGE (Basic General Education); rural and urban areas; public policies; educational needs; social context